Analysis on the effect of shop floor parameters on the effectiveness of preventive maintenance through discrete event simulation - Sheng, L.W. (Universiti Putra Malaysia Press, 2017)
Preventive maintenance (PM) is a predetermined task that constitutes any maintenance actions performed before the quantity or quality of product equipment deteriorates. PM is primarily aimed at protecting assets, improving system reliability, and decreasing system downtime. Recently, the implementation of PM is becoming more challenging due to the increase in complexity of manufacturing systems. A case study on the effect of different parameters from a maintenance perspective on industrial shop floor performance is presented. The parameters include number of technicians, number of operations in each machine before maintenance actions, and volume of parts ordered by customers. This present research demonstrates the application of WITNESS simulation software to develop shop floor simulation model and the use of analysis of variance (ANOVA) to measure the significance of such parameters on performance. © 2017 Universiti Putra Malaysia Press.